Kampung Naga’s Forbidden Forest and Wisdom for Ecological Adaptation Strategy - Mirna Nur Alia Nur Alia Abdullah; Annisa Fadhilah; Anesito Custilas (LPPM Universitas PGRI Sumatera Barat, 2025)
The Kampung Naga indigenous community in West Java exemplifies a conservation model based on local wisdom. For centuries, they have protected a 50-hectare Forbidden Forest. This study aims to examine the Kampung Naga Forbidden Forest as a socio-ecological adaptation system in response to global disruption. Through a qualitative literature review, the study found that this forest, protected by customary laws such as logging prohibitions and the leuit (communal rice barn) system, plays a crucial role in conserving biodiversity, water management, and food security. The study found that this forest conserves 85% of endemic plant species and absorbs millions of liters of rainwater annually. However, increasing external pressures, such as infrastructure development, mass tourism, and the decline of traditional ecological knowledge over generations, have begun to erode its sacred value and sustainability. Traditional rituals such as Sedekah Bumi (Earth Almsgiving) have been commercialized into paid festivals, while youth engagement in ecological customs such as ngaruat (alms-giving rituals) has declined drastically. Using Cultural Ecology and the Social Construction of Reality as theoretical frameworks, this study argues that Kampung Naga's resilience stems from its ability to integrate ancestral beliefs with modern legal instruments and frameworks. The study concludes that the Forbidden Forest is not only a conservation area, but also a cultural and spiritual landscape shaped by the practices of indigenous communities over generations. The novelty of this research, its sustainability, offers valuable insights into community-based ecological strategies in an era of global disruption